Some causal aspects in the decrease of function of the aging heart - Ahmad Muhammad Djoyosugito Ahmad Muhammad Djoyosugito (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
The process of aging of an individual has begun since his existence in the womb. Old age forms the last stage of the process.In this aging process changes take place continuously affecting the morphology and function of the individual, his systems, and organs down to the ultrastructure and biochemical reactions, probably due to